Procurement Practices and Performance of Private Universities in West Nile, Uganda - Hamiza, Olema; Ishaq, Amandu Yassin; Viola, Isaburu; Flavia, Alwayo Bella; Giovanna, Lawino (Business Management and Strategy, 2024)
This study examined the effect of procurement practices on the performance of private universities in West Nile, Uganda. Five private universities dully accredited by the National Council of Higher Education were analyzed. Using simple random sampling technique, a sample size of 140 employees was used. Data were sourced using a structured questionnaire. Analysis was conducted using both SPSS and SEM. The findings revealed that contract management is a significant precursor of private university performance. While unexpectedly, procurement planning and supplier selection proved to be statistically insignificant predictors of private university performance. Practically, this study will help private university owners improve performance by embracing practices such as contract inspection, documentation, relationship management, good communication and contract performance measurement. Additionally, given the need for improved performance of private universities in West Nile in particular, and Uganda in general, this study offers the understanding of a holistic view of performance from the procurement perspective and this is relevant for academicians.